Attachable and flexible aluminum oxide resistive non-volatile memory arrays fabricated on tape as the substrate. (27th February 2017) - Lee, Woocheol; Jang, Jingon; Song, Younggul; Cho, Kyungjune; Yoo, Daekyoung; Kim, Youngrok; Chung, Seungjun; Lee, Takhee
Abstract: We fabricated 8 × 8 arrays of non-volatile resistive memory devices on commercially available Scotch ® Magic ™ tape as a flexible substrate. The memory devices consist of double active layers of Al2 O3 with a structure of Au/Al2 O3 /Au/Al2 O3 /Al (50 nm/20 nm/20 nm/20 nm/50 nm) on attachable tape substrates. Because the memory devices were fabricated using only dry and low temperature processes, the tape substrate did not suffer from any physical or chemical damage during the fabrication. The fabricated memory devices were turned to the low resistance state at ∼3.5 V and turned to the high resistance state at ∼10 V with a negative differential resistance region after ∼5 V, showing typical unipolar non-volatile resistive memory behavior. The memory devices on the tape substrates exhibited reasonable electrical performances including a high ON/OFF ratio of 10 4, endurance over 200 cycles of reading/writing processes, and retention times of over 10 4 s in both the flat and bent configurations.